Współczesne trendy w lingwistyce komputerowej a problem automatycznego tłumaczenia języka arabskiego - Łacina, Jerzy (Investigationes Linguisticae, 2012)
The aim of this paper is to present some problems concerning the machine translation of Arabic in the context of the chosen NLP theories and their evolution. First attempts of electronic machine translations in Europe started only a little more than fifty years ago. It is enough time to perceive some aspects of the evolution? Although a lot of the concepts are still valid, the situation in A.D. 2012 is quite different than even twelve years ago. We still see useful old works of N. Chomsky, D. Cohen, but CFG seems to be supported with some new theories which also have got some disadvantages. Some interesting problems occur in the process of automatic translation when the number of grammatical cases is smaller in the source language than that in the output language.